2012
DOI: 10.1039/c2cc32187d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning delamination of layered covalent organic frameworks through structural design

Abstract: Exfoliation of a family of polyacetylenic porous layered covalent organic frameworks by means of a simple sonication procedure results in the obtention of nanolayer structures as observed by AFM and TEM measurements. Systematic AFM analysis of the isolated nanostructures reveals that the degree of exfoliation depends on the polymer architecture, thinner layers being observed when the pore size decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 26 publications
2
61
0
3
Order By: Relevance
“…63,64 Thus, in 2013, Bunck and Dichtel reported that 2D hydrazone-linked COFs can be exfoliated into 2D-polymers that assemble organic subunits into covalently linked, high-aspect-ratio networks with longrange order. 63,64 Thus, in 2013, Bunck and Dichtel reported that 2D hydrazone-linked COFs can be exfoliated into 2D-polymers that assemble organic subunits into covalently linked, high-aspect-ratio networks with longrange order.…”
Section: Towards 2d-polymers Based On Cofsmentioning
confidence: 99%
“…63,64 Thus, in 2013, Bunck and Dichtel reported that 2D hydrazone-linked COFs can be exfoliated into 2D-polymers that assemble organic subunits into covalently linked, high-aspect-ratio networks with longrange order. 63,64 Thus, in 2013, Bunck and Dichtel reported that 2D hydrazone-linked COFs can be exfoliated into 2D-polymers that assemble organic subunits into covalently linked, high-aspect-ratio networks with longrange order.…”
Section: Towards 2d-polymers Based On Cofsmentioning
confidence: 99%
“…Although numerous COF powder exfoliation methods have been reported, very few of these studies demonstrate the ability to reconstitute the resulting nanosheets into large‐area COF films . Most reported methods involve either sonicating the powders in organic solvents or mechanically grinding the powders prior to dispersion, but due to challenges with re‐aggregation and sedimentation at high concentrations, these strategies typically produce dilute suspensions (≤0.2 mg mL −1 ) that are not conducive to large‐scale film fabrication . Although Tsuru and co‐workers demonstrated that thin films can be prepared from a dilute suspension (0.15 mg mL −1 ) of COF‐1 powder prepared through sonication in dichloromethane, the fabrication process required repeated drop‐casting/drying cycles to form a continuous film, and therefore lacks scalability and practicality .…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization reactions that have the potential to result in robust monolayer macromolecules with laterally extending repeat units have been the subject of numerous studies within the past few years . This concerns both single crystal as well as interfacial approaches using an air/water interface.…”
Section: Introductionmentioning
confidence: 99%